A POTENTIAL INCREASES IN THE PROFITABILITY OF GRAIN PRODUCTION BY MULTIPLE CROPPING SYSTEM IN ATHALAVILAI, KANYAKUMARI DISTRICT, TAMIL NADU, INDIA - SUBITHA SHAJINI R; KIRAN R (The Bioscan, 2025)
This study explores the potential for increasing profitability in grain production through multiple cropping systems in Athalavilai, Kanyakumari District, Tamil Nadu. The primary objective is to compare grain production systems utilizing crop rotation with species diversification against traditional double-cropping systems that lack diversification. By analyzing the productivity and profitability of these systems, the study aims to develop a method for mapping and characterizing multiple cropping systems and estimate the potential for increasing cropping intensity. Furthermore, the research introduces a baseline estimate of multiple cropping area to aid future global and regional studies on cropping systems. The hypothesis posits that species-diversified crop rotations will outperform double-cropping rotations in terms of both productivity and profitability, contributing to enhanced resilience to abiotic stresses and improved resource conservation. The findings of this study are crucial for optimizing sustainable agricultural practices and ensuring long-term profitability in grain production.